How objective and subjective knowledge affect insurance choices. Issue 4 (December 2017) - Kuusela, Hannu; Spence, Mark; Paul, Pallab
Abstract This study investigates the effect of objective knowledge (OK) and subjective knowledge (SK) on real-life insurance choices, a non-trivial, information-rich choice task with no dominant option. Prior research has shown that OK and SK tend to be correlated, but that is not always the case. By using a novel approach to manipulate SK—which could be adapted by salespeople in real-world contexts—we ensured that levels of SK and OK were not always in accord. Clear patterns emerged showing an inverse relationship between SK and OK, and the number of problem-framing (or structuring)-related statements made, number of overall information processing operations performed and the time spent to reach a decision. Most of the extra effort expended by low SK/low OK individuals was spent framing the problem, not executing decision rules such as making attribute comparisons. Those with high OK were also less prone to misunderstanding product information. Whether high or low SK/OK, there were no differences in final choices, suggesting that neither group jumped to a simplifying choice heuristic. Instead, those low in knowledge compensated for this deficiency by taking more time framing the problem and reaching a thoughtful decision, a decision strategy that weakens the effect of branding.